Learning as a conscious process - S.S. Holovatyi (Academy of Cognitive and Natural Sciences, 2009)
In article it із spoken about such training in which result, the higher school would receive shots of highly formed experts which freely and intelligently used the knowledge and abilities, and have been for ever deprived standard habits and the stereotypes capable for the further development and professional growth.